Generation of an Ultra-Long Optical Needle Induced by an Azimuthally Polarized Beam - Liwei Liu; Lifang Shi; Fanxing Li; Siyang Yu; Simo Wang; Jialin Du; Min Liu; Bo Qi; Wei Yan (IEEE Photonics Journal)
In this manuscript, a method of generating an ultra-long optical needle (depth-to-width ratio 37.5:1) is proposed and demonstrated by focusing an azimuthally polarized beam. In theory, the action mechanism between the incident beam and the amplitude modulation element, the spiral phase modulation element, the focusing lens were studied based on the Richards and Wolf's theory. The relationship between the intensity distribution of the optical needle and the structure parameter of the element were obtained, thus leading to the complete design model and design standard. In experiment, the annular amplitude modulation element and spiral phase modulation element were fabricated by lithography. The optical needle was obtained based on a custom-designed optical setup in our laboratory. The optical system consists of an annular aperture (3.9-mm inner diameter, 80-µm annular width), a spiral phase plate (topological charge of 1), and an objective lens with numerical aperture of 0.95. Finally, an optical needle with a subwavelength size (0.416λ) and an ultra-long depth of focus (15.6λ) was obtained, showing an excellent agreement with our theoretical model.